PI3K/AKT signaling in parasites and parasite diseases: Role and therapeutic potential - Lujun Yan; Yating Li; Xing Yang; Rui Li; Chunyin Zhu; Xuedong He; Xiaoliang Jin; Guanghui Zheng; Naunain Mehmood; William C. Cho; Shijun Bao; Houhui Song; et al. (Virulence)
Parasite diseases pose a significant threat due to the serious harm they cause to hosts, and developing affordable drugs for treatment presents enormous challenges. “Target repurposing” has emerged as a promising strategy to overcome this difficulty by leveraging the drug targets for human diseases and matching them with homologs in parasites. The PI3K/AKT signaling pathway, known for its crucial role in regulating malignant cell proliferation, migration, and invasion, has been validated as a drug target for cancer. Interestingly, the PI3K/AKT signaling pathway is also involved in parasite development, infection, and survival within the hosts. During infection, parasites can exploit the host’s PI3K/AKT signaling, which influences immune cell apoptosis, macrophage activation, regulatory T cell functions, and the communication between immune cells, thus facilitating chronic infection. The immunoregulatory functions of the PI3K/AKT signaling make its inhibitors promising candidates for the control of parasite diseases. This review mainly outlines the characteristics and functions of the PI3K/AKT signaling pathway during parasite infection and further provides an overview of the drugs targeting the PI3K/AKT signaling pathway for treating parasite diseases.